Population Pharmacokinetic Modelling of Orally Administered Doxycycline to Rabbits at Different Ages - Rositsa Mileva; Anton Rusenov; Aneliya Milanova (MDPI AG, 2021)
Doxycycline is a well-tolerated tetracycline antibiotic, registered for use in rabbits and administered for treatment of bacterial infections in this animal species. Nevertheless, the available pharmacokinetic data are limited and this study aimed to investigate the pharmacokinetics of orally administered doxycycline in mature and immature rabbits by application of the population approach. The rabbits were treated orally with doxycycline hyclate (5 mg/kg bw) in the form of a solid gelatin capsules. Free plasma concentrations were determined with HPLC analysis with Photodiode array detection. The estimated typical value of volume of distribution (tvV), total body clearance, and absorption rate constant were 4.429 L/kg, 1.473 L/kg/h, and 0.257 h−1, respectively. The highest between-subject variability (BSV) of 69.30% was observed for tvV. Co-variates such as body weight, age, and biochemical parameters did not improve the tested model and did not contribute to explanation of the BSV. The population pharmacokinetic model of the orally administered doxycycline in rabbits should be further developed by addition of data from more animals treated with higher doses. An oral dose of 5 mg/kg could ensure percentage of the time from the dosing interval during which the concentration is above minimum inhibitory concentration (MIC) %fT > MIC of 35% if MIC of 0.18 μg·mL−1 and a dosing interval of 12 h is assumed which does not cover criteria for rational use of antibiotics.